2014
DOI: 10.5539/gjhs.v6n5p81
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Disparities in Access to Health Care in Iran: Evidence from Lorestan Province

Abstract: Equal distribution of healthcare facilities in order to increase the accessibility of the individuals to services is one of the main pillars in improvement of health. This study was aimed to examine the disparities in access to health care services across the cities of Lorestan province located in west of Iran. This study is a descriptive study. Data related to indicators of institutional and manpower was collected using statistical yearbook of Statistical Centre of Iran (SCI) and analyzed by Scaogram Analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 14 publications
(12 reference statements)
0
10
0
1
Order By: Relevance
“…Amini et al [24] stated that Isfahan and Tehran had high The results of this study revealed a significant difference between the Iranian provinces in terms of their health facility development levels. Overall, the results of most studies exploring this field also indicated that the health sector resources were inadequately distributed [16,26,27].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Amini et al [24] stated that Isfahan and Tehran had high The results of this study revealed a significant difference between the Iranian provinces in terms of their health facility development levels. Overall, the results of most studies exploring this field also indicated that the health sector resources were inadequately distributed [16,26,27].…”
Section: Resultsmentioning
confidence: 99%
“…CoCoSo is a technique for prioritizing a set of alternatives by the combination of simple additive weighting and an exponentially weighted product model. The CoCoSo method provides simpler and easier steps and eliminates the weaknesses of other MCDM methods such as TOPSIS or COPRAS (26). This method has been used in various contexts such as supplier selection [21,22] and health sector evaluation [23].…”
Section: Combined Compromise Solution (Cocoso) Methodsmentioning
confidence: 99%
“…[12] People in the United States experience huge disparities in availing health care services and also with health outcomes [13][14][15] which can be comparable to the people in low-income and developing nations who experience widespread disparities in healthcare. [16][17][18][19][20][21][22][23][24] Findings of this study are very helpful in understanding factors of dissatisfaction with healthcare models in several countries. However, there is very limited research on this subject, which limits us in comparing findings of this research.…”
Section: Discussionmentioning
confidence: 99%
“…Berdasarkan hasil analisis skalogram dari penelitian Nemati et al (2014) adanya kesenjangan pada pelayanan kesehatan di provinsi Lorestan. Pengurangan kesenjangan pelayanan kesehatan harus diperhatikan karena wilayah yang terbelakang dikarenakan kurangnya perencanaan program di wilayah tersebut.…”
Section: Pendahuluanunclassified